Transport and metabolism of acetate in rat brain cortex in vitro - Gonda, O. (1966)
1. [1-(14)C]Acetate undergoes metabolism when incubated aerobically at 37° in the presence of rat brain-cortex slices, forming (14)CO(2) and (14)C-labelled amino acids (glutamate, glutamine, aspartate and relatively small quantities of γ-aminobutyrate). In the absence of glucose the yield of (14)C-labelled aspartate exceeds that of (14)C-labelled glutamate and glutamine. The addition of glucose brings about a doubling of the rate of formation of (14)CO(2) and a greatly increased yield of (14)C-labelled glutamate or glutamine, whereas that of (14)C-labelled aspartate is diminished. 2. The addition of potassium chloride (100mm) to the incubation medium causes an increased rate of (14)CO(2) formation in the presence or absence of glucose and an increased rate of utilization of acetate. 3. The addition of 2,4-dinitrophenol (0·1mm) suppresses the rate of utilization of [1-(14)C]acetate. 4. The presence of ouabain (10μm) suppresses the rate of formation of (14)CO(2) from [1-(14)C]acetate and the rate of acetate utilization. Acetate conversion into carbon dioxide in the rat brain cortex is both Na(+)- and K(+)-dependent and controlled by operation of the active sodium-transport process. Only the Na(+)-stimulated rate is suppressed by ouabain. 5. Sodium fluoroacetate (1mm) decreases the rate of (14)CO(2) evolution from [1-(14)C]acetate in the presence of rat brain cortex without affecting the respiratory rate. The results are consistent with the conclusion that fluoroacetate competes with, or blocks, a transport carrier for acetate, so that in its presence only the passive diffusion rate of acetate takes place. 6. The presence of sodium propionate or sodium butyrate suppresses the utilization of [1-(14)C]acetate in rat brain cortex and leads to a concentration ratio (tissue/medium) of [1-(14)C]-acetate greater than unity. 7. The presence of NH(4)(+) diminishes acetate utilization, this being attributed to a diminished ATP concentration. Glycine is also inhibitory. It is concluded that acetate transport into the brain is carrier-mediated and dependent on the operation of the sodium pump.